Analysis a Failure of Paired Widya Kandi and Moh Hilmi in Elections Regent Kendal 2015 - Arvyn Galang Prakasa; Fitriyah . .; susilo utomo . (Journal of Politic and Government Studies, 2017)
Elections are a way in a country that adheres to the election for public officials. The elections or the election in Indonesia is a general election to elect the regional head and deputy head of the region directly by local residents who qualify. On December 9, 2015 local elections held simultaneously for the first time, including Kendal. In the elections is certain there will be candidates who won and the defeated pair. The focus of this study is to discuss about the failure of incumbent Widya Kandi with a pair deputy candidates Moh Hilmi. The method used in this research is Qualitative. Research sites in Kendal regency. The method of collecting the data in this study by interviewing informants involved in Kendal 2015 election.             Results from the study showed some factors failure of incumbent Widya Kandi. (1) The role of political parties in the process of winning was less effective. (2) Performance Widya Kandi incumbent in office less well, especially the issues of infrastructure development that is less realized, making communities Moh Hilmi figures disappointed and very new in world politics make less known by the public. (3) The strategy used by less than the maximum campaign team made no significant noise increase. (4) Wdya Kandi attacked by a black campaign issues that make her electability down.  Key words: Election, Failure, Analysis